Analisis Preferensi Incoterms dan Payment Terms Untuk Transaksi Ekspor di Kalangan Eksportir : Studi Kasus Menggunakan Survei Online - Abdillah, Nur Muhammad (Maliki Interdisciplinary Journal, 2026)
This study is entitled ‘Analysis of Incoterms and Payment Term Preferences for Export Transactions among Exporters: A Case Study Using an Online Survey’. The purpose of this study is to identify the Incoterms and Payment Terms most commonly used by exporters in Indonesia, as well as to analyse the factors that influence their preferences. The research method used was a quantitative approach with an online survey distributed through the Instagram account @overheardekspor, involving 33 respondents who were export companies. The survey results found that the most frequently chosen Incoterm was FOB (Free On Board), selected by 16 respondents, while the most frequently chosen Payment Term was Telegraphic Transfer (TT), selected by 26 respondents. The main reasons for choosing Incoterms were lower risk (51.5%) and ease of administration (48.5%). Meanwhile, the main reasons for choosing Payment Terms were transaction security (72.7%) and speed of payment (57.6%). The biggest challenges faced by respondents in choosing Incoterms and Payment Terms were transaction risk (60.6%) and regulatory differences (33.3%). Most respondents suggested choosing Incoterms class C and D as well as Payment Term TT to obtain greater profits with careful consideration of the risks. These findings are expected to provide guidance for exporters in choosing the right Incoterms and Payment Terms to reduce risks and increase efficiency in export transactions.